The Practicality of Teaching Materials on Types of Crab in the Mangrove Forest Area to Improve Critical Thinking Skills for Islamic High School Students - Nahri Fauzan; Mochamad Arief Soendjoto; Muhammad Zaini (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The crabs are organisms that have a major role in the mangrove ecosystem. The preservation of the mangrove ecosystem cannot be separated from the roles and responsibilities of humans. This can be started by creating awareness and practicing thinking skills to provide solutions to various existing environmental problems. According to the results of the TIMSS study, the low scientific ability of Indonesian students, especially its implementation in the form of scientific literacy, has not shown a good improvement so that learning innovations are needed, one of which is the manufacture of environment-based teaching materials. The purpose of this study was to describe the practicality of the teaching materials